A comparative study of the impact of violations of public law on concluded public contracts - Christidis, Aris (2019)
A highly interesting and controversial question in the regulation of public contracts is what follows in that situation where a contract has been concluded unlawfully, that is, in breach of those rules of public nature that regulate the contractual activity of public authorities.